Les genres journalistiques d’aujourd’hui - Maurizio Alì (Communiquer)
This reference work presents the process of informative production and its three pillars: the journalist, the distribution platforms and the informative genres. Structured as a journalism manual, it is in fact a scholarly work that will interest researchers and professionals who wish to understand the challenges of global communication and discover the latest research works published in Spanish.